The Influences of Financial Distres and Internal Control on Earnings Management with Good Corporate Governance as a Moderating Variable - Fathiha, Ananda Ulvira; Alimuddin, Alimuddin; Usman, Asri (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study investigates the effects of financial distress and internal control on earnings management, considering good corporate governance as a moderating factor. The research targets primary consumer goods firms listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2023. The objective is to evaluate the influence of financial distress and internal control on accrual-based earnings management using a quantitative approach and path analysis. The findings indicate that financial distress has a significant positive impact on accrual earnings management but does not affect real earnings management. In contrast, internal control negatively influences accrual earnings management, without significantly impacting real earnings management. Furthermore, good corporate governance moderates the effects of financial distress and internal control on accrual earnings management but does not extend this moderating effect to real earnings management. These results enhance the understanding of the moderating role of good corporate governance in managing earnings practices.Keyword:Financial Distress, Internal Control, Good Corporate Governance, Earnings Management